Impact of Compensation and Financial technology Against Employee Performance Mediated by Employee Job Satisfaction - Wike Pertiwi; Dwi Epty Hidayaty (International Journal of Ecma Science, 2021)
This observation targets to take a look at the impact of compensation and financial technology on employee performance mediated through employee job satisfaction. In addition, this observation additionally targets to take a look at the impact of compensation and financial technology on job satisfaction, the impact of job satisfaction on overall performance, the impact of compensation on overall performance, and the impact of financial technology on overall performance. The hypothesis takes a look at used is direction analysis with the Bootstrap resampling technique the usage of the t-take a look at the statistic. This type of study is causal-comparative with a quantitative method designed inside the shape of survey studies through distributing questionnaires to eighty employees of a personal financial institution as a sample on this studies. The variables on this observation are compensation and financial technology as exogenous variables, job satisfaction as an intervening variable, and overall performance as an endogenous variable. The results confirmed that compensation and monetary generation have a partial and simultaneous have an effect on job satisfaction, job satisfaction has an advantageous and significant effect on overall performance, repayment has a significant advantageous impact at once and in a roundabout way on overall performance, even as financial technology has no direct have an effect on overall performance. overall performance however if it's miles mediated through job satisfaction, financial technology will make a contribution a significant impact.